2018
DOI: 10.1371/journal.pone.0191171
|View full text |Cite
|
Sign up to set email alerts
|

Stentless vs. stented bioprosthesis for aortic valve replacement: A case matched comparison of long-term follow-up and subgroup analysis of patients with native valve endocarditis

Abstract: BackgroundCurrent retrospective evidence suggests similar clinical and superior hemodynamic outcomes of the Sorin Freedom Solo stentless aortic valve (SFS) (LivaNova PLC, London, UK) compared to the Carpentier Edwards Perimount stented aortic valve (CEP) (Edwards Lifesciences Inc., Irvine, California, USA). To date, no reports exist describing case-matched long-term outcomes and analysis for treatment of native valve endocarditis (NVE).MethodsFrom 2004 through 2014, 77 consecutive patients (study group, 59.7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The major findings of this review noted that surgical correction of aortic valve endocarditis ranged around 55% per year and in high-income nations, most of the patients involved were >60 years. There is a general preference for biological prostheses 18,26,31 as the primary intervention over mechanical prostheses 27,115 and homografts or autograft. 28,32,34,47 Aortic valve repair is indicated in selected cases and the use of the TAVR is not recommended in current guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…The major findings of this review noted that surgical correction of aortic valve endocarditis ranged around 55% per year and in high-income nations, most of the patients involved were >60 years. There is a general preference for biological prostheses 18,26,31 as the primary intervention over mechanical prostheses 27,115 and homografts or autograft. 28,32,34,47 Aortic valve repair is indicated in selected cases and the use of the TAVR is not recommended in current guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, better outcomes with the SS stentless valve depend on optimal patient selection and on recognizing its limitations. 8,11) In conclusion, high-risk patients with infective endocarditis accompanied by annular abscess, a small aortic annulus, and those who require concomitant mitral valve surgery and redo AVR may profit from SS stentless valve implantation.…”
Section: Discussionmentioning
confidence: 97%
“…6) Recently, the FS bovine pericardial stentless valve has been used for the surgical treatment of infective endocarditis. [7][8][9] A recent multicenter study showed the surgical results of 59 patients with extensive infective endocarditis who underwent AVR with the FS bovine pericardial stentless valve. 7) All patients in this study presented with annular tissue infection, and 54.3% of them had annular abscess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while the implantation of stented BPHVs is easier, especially through the small aortic root, surgical implantation of stentless valves is more difficult and time-consuming. In a recent study by Schaefer and colleagues, superior hemodynamic characteristics of stentless aortic valves in comparison to a stented aortic valve was confirmed, however, the rate of SVD occurrence and subsequent endocarditis was higher in patients who received stentless valves (Schaefer et al, 2018).…”
Section: Bio-prosthetic Heart Valves (Bphvs)mentioning
confidence: 94%